The Role of Sensation Seeking in Substance Use and Sporting among Female Teachers Training College Students - Pikó, Bettina F.; Pinczés, Tamás (European Journal of Mental Health, 2019)
Sensation seeking is a personality trait characterized by the need for novelty, adventure, and a general willingness to take risks. Young adults are more likely to seek sensations in high-risk situations, such as shared substance use among friends, risky sexual behavior, or sports. We know even less about any link between behaviors that are not necessarily risky (e.g., hobby sporting, occasional drinking, etc.) and gender characteristics. This paper explored the role of different dimensions of sensation seeking in female college students’ health behavior, including smoking, drinking, and active sporting. The sample consisted of female teachers training college students from Debrecen, Hungary (N = 171; mean age = 20.6, S.D. = 2.6 years). Binary logistic regression analyses revealed that the total score on the sensation seeking scale (BSSS-8) was related to all types of health behavior. Disinhibition (D) contributed to smoking and drinking, while other dimensions were also related to smoking. In addition, in active sporting Experience Seeking (ES) played a role. Focus on different dimensions of sensation seeking can be applied in health education programs, particularly for students (teacher training) whose health behavior may serve as an exemplar for children. As multiple analyses suggest, sport motivation can be elevated through satisfying the female students’ experience seeking, while skills training in disinhibition may help to reduce their substance use.